Ion composition in interchange injection events in Saturn's magnetosphere. Issue 12 (11th December 2014) - Thomsen, M. F.; Reisenfeld, D. B.; Wilson, R. J.; Andriopoulou, M.; Crary, F. J.; Hospodarsky, G. B.; Jackman, C. M.; Jia, X.; Khurana, K. K.; Paranicas, C.; Roussos, E.; Sergis, N.; et al.
Abstract: Interchange injection events are commonly observed by the Cassini spacecraft in the region between about 6 and 12 Rs (1 Rs  = 60, 268 km) and even frequently beyond. In this study, 13 examples of interchange injection events are identified in Cassini/Cassini Plasma Spectrometer data under special conditions such that time‐of‐flight (TOF) mass spectra could be obtained from entirely within the events. Using the TOF data to separate the main ion species H +, H2 +, and W +, approximate densities of each species are calculated under the assumption that all distributions were isotropic. The light‐ion density ratios, H2 + /H +, in the injection events are not discernibly different from those ratios in control intervals from the ambient plasma. However, the water‐group ratio, W + /H +, is significantly lower than ambient. The comparison of the measured density ratios with the range of values observed throughout Saturn's magnetosphere indicates that the values of W + /H + that are as low as those observed within the injection events are found primarily beyond L ~14 (where L is the equatorial crossing distance, in Saturn radius, of a dipole field line), indicating that the injection events are delivering plasma from the outer magnetosphere at times traveling at least 6 Rs . Key Points: Ion composition (H2 + /H + and W + /H + ) is measured in 13 interchange injections W + /H + is significantly reduced compared to nearby inner magnetospheric plasma The composition suggests an injection origin beyond L~14